New species and record of Zygophiala (Capnodiales, Mycosphaerellaceae) on apple from Montenegro - Zhang, Mian; Gao, Liu; Shang, Shengping; Han, Xiaolu; Zhang, Rong; Latinović, Jelena; Latinović, Nedeljko; Batzer, Jean Carlson; Gleason, Mark L.; Sun, Guangyu (Phytotaxa, 2015)
Species of Zygophiala are components of the sooty blotch and flyspeck complex that blemish the cuticle of fruits reducing their economic value. In our study, six strains were isolated from apple fruit collected in orchards in Montenegro. Zygophiala montenegroensis is a newly described species based on its unique morphological characteristics and the analysis of multiple sequences including the internal transcribed spacer of the rDNA, the partial translation elongation factor 1-alpha and the actin genes. Zygophiala cylindrica is described as a new record in Montenegro and Europe.